Analysis and Control Technology of blue Smoke in Coal-fired Power Plants. Issue 3 (February 2020) - Guo, Liqiang; Yan, Hanbing; Li, Yongxiang; Chen, Xiufang; Liu, Fengchun
Abstract: The control of blue Smoke in coal-fired power plants is of great significance to the atmospheric environment. The emission of SO3 from coal-fired power plants is an important factor of blue Smoke production, which mainly comes from boiler combustion and selective catalytic reduction (SCR) denitration. When the content of SO3 in the flue gas is too high, it will cause problems such as dust accumulation, low-temperature acid corrosion, increased air preheater resistance, and degraded performance of the electric precipitator, which will affect the economical efficiency and safety of the unit. In this paper, the causes of blue Smoke in coal-fired power plants are analyzed, the conversion rate of SO3 is calculated and verified, and technical measures to control colored plumes are proposed.